Morphometric Variations in Limonia acidissima Fruits and Seeds - Implications for Conservation and Tree Improvement - Anandalakshmi, R.; Santhiya, R.; Aarthi, M.; Vineetha, M. V.; Suresh Kumar, K.; Sathish, A. (Indian Forester, 2025)
Limonia acidissima or Wood apple is a promising wild edible fruit which can extend livelihood support. This study delves into intra-species diversity studies confining to morphometric variations in fruits and seeds of wood apple from diverse seed sources in Tamil Nadu, through image analysis system. Fruit and seed morphometric parameters were analyzed, revealing statistically significant differences among 6 seed sources such as Ariyalur, Perambalur, Thiruvannamalai, Trichy, Vellore and Virudhunagar. Perambalur and Thiruvannamalai stood out for producing larger fruits, while Vellore and Perambalur yielded larger seeds. The correlation and cluster analysis further unveiled intricate relationships among fruit and seed characteristics, highlighting associations between size, shape, and germination potential. These findings not only provide valuable insights for tree improvement efforts but also contribute to enhancing the economic and ecological significance of underutilized fruits like Limonia acidissima.